The Quality Shift: A Sociological Approach to the winemaking in the Province of Teramo, Abruzzo and the possible development through wine tourism - Spineti, Greta; Nico Bortoletto (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article retraces the history of development of winemaking in Abruzzo, a region in central Italy, through bibliographic research. It focuses on the paradigm shift adopted during the second half of the past century when winemakers began to shift towards the production of quality wine, even at the expense of quantity. The theoretical background on modern society and its implications with traditions and innovations stems from Beck et al. (1997), where tradition is considers to be a means to replicate the past. The hypothesis here is that the cultural heritage represented by wine, winemaking and what these can create (i.e., the landscape) can become true drivers for tourism in Northern Abruzzo, as they did in Mendoza, Argentina. In the context of regional development and innovation, there is a hope for a greater emphasis on wine tourism, capable of bringing about social and economic development and greater protection of the territory, as seen in Argentina. The investigations reveal the untapped potential of the Italian region, mainly due to technological setbacks. In this sense, literature supports the idea that The wine roads could be a valid way to promote and develop local culture and heritage.